Immune response to influenza vaccination in the elderly is altered by chronic medication use - Divyansh Agarwal; Kenneth E. Schmader; Andrew V. Kossenkov; Susan Doyle; Raj Kurupati; Hildegund C. J. Ertl (Immunity & Ageing, 2018)
Abstract Background The elderly patient population is the most susceptible to influenza virus infection and its associated complications. Polypharmacy is common in the aged, who often have multiple co-morbidities. Previous studies have demonstrated that commonly used prescription drugs can have extensive impact on immune defenses and responses to vaccination. In this study, we examined how the dynamics of immune responses to the two influenza A virus strains of the trivalent inactivated influenza vaccine (TIV) can be affected by patient’s history of using the prescription drugs Metformin, NSAIDs or Statins. Results We provide evidence for differential antibody (Ab) production, B-cell phenotypic changes, alteration in immune cell proportions and transcriptome-wide perturbation in individuals with a history of long-term medication use, compared with non-users. We noted a diminished response to TIV in the elderly on Metformin, whereas those on NSAIDs or Statins had higher baseline responses but reduced relative increases in virus-neutralizing Abs (VNAs) or Abs detected by an enzyme-linked immunosorbent assay (ELISA) following vaccination. Conclusion Collectively, our findings suggest novel pathways that might underlie how long-term medication use impacts immune response to influenza vaccination in the elderly. They provide a strong rationale for targeting the medication-immunity interaction in the aged population to improve vaccination responses.